Aproveitamento do cascalho de perfuração de poços para elaboração de pasta de cimentação primária - Almeida Neto, José Bezerra de (2017)
The oil industry, in all its segments has the potential to cause environmental impacts. One major impact on the physical environment, generated by the oil industry, is associated with the drilling of oil wells due to the waste generation, among which are the drilling fluid and cuttings resulting from oil well drilling. It is estimated that in Brazil's Northeast region currently exists a waste quantity in the order of 100,000 m³ coming from land drilled wells for oil production and also due to the increasing well numbers, it is presumed a generating of 50 m³ by year. Due to the drill cuttings amount and its organic and inorganic contaminants generated, as well as the treatment, transportation, disposal and associated costs, there is usually a backset in the solid waste management, such as the adequacy of the drill cuttings produced volume over a period of time versus the evaluation and release times of the destined area to the industrial landfill, by the State's control and inspection, aiming at the reception and maintenance safe of these wastes. The present study aims to analyze the technical feasibility of the drill cuttings wastes adding (DCW) in the cement slurry, used in oil wells. The cement slurry physicochemical properties with drill cuttings depicted in this study are the lab test results carried out to adapt them to the technical parameters established by the oil company. The cement slurry lab tests done were: density, rheology, filtrate, free water, thickening time, stability and compressive strength. Some relevant results are described below. Some relevant results are described below, with the focus on the raise of 8% in the yield of the examined cement slurries with drill cuttings, compared to the conventional cement slurries, for a given density. The compressive strength of these cement slurries, under the investigated well conditions, reaches, at least, 2600 psi in up to 29 hours. The technological innovation presented in this study, according to the technical framework required by oil company for cement slurry used in primary cementing for producer intervals, proves to be feasible economically, since the introduction of 10% of drilling cuttings into the cement slurry composition provides a cement slurry cost reduction by produced volume, as a result of the cement content and related chemicals decreases, as well as the reduction of over 80% in the drill cuttings processing cost to the oil drilling contractors, due to the lower waste volume destined for controlled landfills. In addition, such an initiative can be considered fair socially because it creates an investment opportunity for the drill cuttings processing by society, through partnerships or cooperatives, enabling the employment and income generation; And sustainable environmentally, by reducing the drill cuttings disposal to the environment, whether by industrial landfill disposal or underground injection.